PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KEPRIBADIAN PESERTA DIDIK DI SMP AL HASIB PAKIS MALANG - Nisfiawati Nisfiawati; Muhammad Hanief; Kukuh Santoso (VICRATINA, 2022)
Education in the early stages of adolescence is the basic foundation for a child's personality leading to maturity.  The values that have been instilled will have an influence on the human personality, so that it manifests itself in outward behavior. In accordance with the results of the research in the title of the role of Islamic religious education teachers, the overall condition of the personality of students at Al Hasib Pakis Junior High School has good morals but some students experience a decline in behavior, students have noble and religious personalities and are in a better direction.  Islamic religious education teachers become role models for students so as to provide motivation to students, advice, space and set a good example.  The supporting factors in shaping the personality of students are providing insight and teaching politeness and courtesy, having good friends and religious activities such as praying together, istighosah, pilgrimage.  Factors inhibiting the progress of science and technology such as cellphones, the environment outside of school and playmates and the lack of attention and motivation of parents towards students.  This study uses a qualitative approach with a descriptive method.  The main data sources (primary) are teachers and students, the second source (secondary) data about the object of research, school document data, photos of learning activities at SMP Al Hasib Pakis Malang, data collection techniques using observation, interviews and documentation.  And the data analysis used is the interactive model of Miles and Huberman.